The difference that transnational and intersectional black feminisms make: a commentary on Tripp. (2nd April 2016) - Ifekwunigwe, Jayne O.
Abstract : In contemporary feminist theories, transnational and intersectional feminisms occupy contested territory. Feminist analyses that are situated exclusively within local and national domains and obscure the lived impact of globalizing economic and political forces also stand on shaky ground. In the following commentary, I will address Tripp's nation-centered framing of difference feminisms in specific and relational geopolitical contexts. By resituating the author's analysis within ongoing debates in feminist theory about the effectiveness of transnational and intersectional black feminist analyses, I will unsettle the conceptual tidiness of her argument.